Diversity and compositional differences in the oral microbiome of oral squamous cell carcinoma patients and healthy controls: a scoping review - van Dijk, M. C.; Petersen, J. F.; Raber-Durlacher, J. E.; Epstein, J. B.; Laheij, A. M. G. A. (Frontiers in Oral Health, 2024)
Objectives The human oral microbiome may play a role in the development of oral squamous cell carcinoma. The aim of this scoping review was to examine microbial diversity and differences in the composition of the oral microbiome between OSCC patients and healthy controls. Methods A literature search (in PubMed and Embase.com) was performed on January 9, 2023. The outcome variables used from the included studies of this review were alpha- and beta diversity and oral microbiome composition profiles for each taxonomic level (phylum-, class-, order-, genus- and species level). Results Thirteen out of 423 studies were included in this review compromising 1,677 subjects, of which 905 (54.0%) were OSCC patients and 772 (46.0%) were healthy controls. Most studies found a higher alpha diversity in the OSCC patient group and significantly different beta diversities between OSCC patient samples and healthy control samples. Studies reported more abundant Fusobacteria (on phylum level), Fusobacterium (on genus level), Fusobacterium nucleatum, Porphyromonas endodontalis and Prevotella intermedia (on species level) in OSCC patients. The healthy control group had more abundant Actinobacteria (on phylum level), Streptococcus and Veilonella (on genus level) and Veilonella parvula (on species level) according to most studies. Conclusions Our findings show differences in oral microbiome diversity and composition in OSCC patients. Clinical implications demand continuing study. Development of internationally accepted standard procedures for oral sample collection and oral microbiota analysis is needed for more conclusive and clinically relevant comparisons in future research.